FACTORS RELATED TO STUNTED TODDLERS IN EASTERN INDONESIA - Ratna Dwi Wulandari; Agung Dwi Laksono (Pusat Penelitian dan Pengabdian Kepada Masyarakat Poltekkes Kemenkes Maluku, 2023)
Background: Eastern regions have a higher prevalence rate of stunted children than other regions in Indonesia. Objective: The study analyzes the factors related to stunted toddlers in Eastern Indonesia. Methods: The study employed secondary data from the 2017 Indonesia Nutritional Status Monitoring. We analyzed 24,103 toddlers as a sample. The study analyzed data using a multinomial logistic regression test. Results: The study found that toddlers living in urban areas had a 0.798 times less chance than toddlers residing in rural areas to experience severe stunted (AOR 0.798; 95% CI 0.719-0.885). A toddler with a married mother is 0.706 times less likely than a toddler with a divorced/widowed mother to experience severe stunted (AOR 0.706; 95% CI 0.547-0.911). The results indicate that the better a mother's education level, the less likely it is to have stunted and severely stunted toddlers. The study also found that toddler age is related to stunted and severe stunted toddlers. The study concluded four factors related to stunted toddlers in eastern Indonesia. The four factors were the type of residence, the mother's marital and education status, and the toddler's age. Conclusion: The study conclusion provides policy targets for policymakers to reduce stunted toddlers in eastern Indonesia, i.e., toddlers living in rural areas, toddlers with divorced/widowed mothers, and toddlers with poor education mothers.